Highway Engineering Composite Material and Its Application - Yao, Jialiang; Zhou, Zhigang; Zhou, Hongzhuan (Springer Nature Singapore : Imprint: Springer, 2019)
This textbook focuses on the performance and application of highway engineering composite material. It collects and compiles the data obtained by the authors in numerous recent practical and research projects in the field of technology and application of highway engineering composite materials in China. It provides valuable reference materials for students and engineering technicians taking courses on the selection, design and construction of composite materials for highway engineering. It offers solutions to various practical engineering problems, and also includes in-depth theoretical analyses of related issues in simple language. Some of the concepts and applications, such as the highway pavement functional layer and the application of polymer composite material to protection of soft rocks, have not been previously covered in the literature before, and as such the book provides engineering and technical professionals with a new vision and new methods. Further, it not only explains the basic concepts, principles, and requirements of composite material for highway engineering, but also describes its application, including the related theoretical analyses, design and construction, making it ideal as a reference book for technical personnel, as well as a textbook for undergraduates and postgraduates majoring in highway engineering.